Adapted overall equipment effectiveness for evaluating loading and hauling equipment performance in open-pit coal overburden removal - Raihan Mhd Indrawan; Riam Marlina; Jukepsa Andas; Rizto Salia Zakri (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Proper equipment functioning is essential to achieving overburden-removal targets in open-pit coal mining, yet independent assessments of Overall Equipment Effectiveness (OEE) for loading-hauling fleets at small Indonesian coal contractor operations remain scarce. This single-site, single-period descriptive case study quantified the productivity of one excavator and four dump trucks engaged in overburden-removal work at BBMM, Jambi, Indonesia, and simulated the potential productivity gain from raising OEE to the 85% world-class benchmark. Cycle times were sampled from ten independent field observations per hauling unit and four documented sub-phases per loading cycle, cross-checked against company production records. Primary data (cycle time, effective working hours) and secondary data (production targets, equipment records) collected in June 2025 were analyzed descriptively using an adapted OEE formulation (Availability × Utilization × Speed × Bucket Fill Factor) suited to BELT (belt-based excavating, loading, and transport) equipment, followed by scenario-based simulation at 85% OEE. Actual overburden production reached 213,566.96 BCM against a target of 216,036.00 BCM, a shortfall of 2,469.04 BCM (98.86% achievement). Adapted-OEE values across all units ranged from 71.2% to 75.2%, below the 85% benchmark, with utilization identified as the primary limiting factor. The 85% OEE scenario indicated potential productivity gains of up to 8,341 BCM/month for the excavator and 1,606–2,268 BCM/month for the dump trucks, corresponding to a 13–19% possible monthly production increase over current performance. Utilization losses, rather than mechanical unavailability, were found to be the main constraint on fleet efficiency, suggesting that targeted dispatching, reduced standby time, and effective-hour management offer greater production leverage than expanding maintenance staffing. This study offers a diagnostic approach applicable to similar small-fleet coal contractors facing overburden-removal shortfalls.